The effectiveness of social training in individuals with autism spectrum disorder (ASD): a systematic review and transfer analysis - Vahid Nejati; Aida Peyvandi; Nasim Nazari; Fatemeh Abadi (Scientific Reports)
Abstract Autism spectrum disorders (ASD) are characterized by impaired social communication and interactions, as well as constrained and repetitive manifestations of interests and behaviors. Various interventions at cognitive and behavioral levels aim to address impaired social communication and interaction in individuals with ASD. This study systematically explores the transferability of social training in individuals with ASD, guided by the conceptual model known as the FIELD framework (Function, Implement, Ecology, Level, and Durability). Employing the PRISMA methodology, 52 original experiments were included in the study. The transfer analysis, formulated as a conceptual meta-analysis based on the effect sizes, underscores the significant impact of variables including age, severity of autism, intervention tools, intervention intensity, intervention context, and intervention duration on the transferability of social training in individuals with ASD. The transfer of skills was particularly conspicuous among younger individuals, especially in face-to-face interventions, in contrast to digital alternatives. Moreover, cognitive interventions exhibited superior transferability compared to behavioral interventions, especially when administered with a higher intervention dose.